Early Detection of Mental Health of Doctoral Students UAD due to the Covid-19 Pandemic through the Questionnaire Method - Agita Hutomo, Muhammad; Nurani, Laela Hayu; Desvita, Widea Rossi; Sikumbang, Isabella Meliawati (Ahmad Dahlan Medical Journal, 2022)
Stress and a decrease in student learning achievement can be triggered by the mal-adaptive coping experienced, especially during the COVID-19 pandemic which requires students to adjust physically and psychologically in the learning process on campus which is now done online and is more independent in learning. So, psychological support for students, especially UAD doctoral students, needs to be done, one of which is mental health screening. The purpose of this study was to determine the mental health condition and social support of students. In the end, this will be the basis for providing psychological support and improving educational and learning activities for UAD Doctoral program students. The research method used was the adjustment and validation of the Self-Report Questionnaire (SRQ) 29, covering aspects of mental health, namely anxiety, depression, stress, use of psychostimulants/substances, symptoms of psychosis (reality rating disorder) and post-traumatic stress disorder (PTSD); Customize and validate social support questionnaires; Submission of ethical review; and Conducting an online survey of mental health, anxiety, depression and social support for Doctoral students. The results obtained from SRQ29 showed that as many as 30% of students experienced PTSD and 10% experienced depression. However, the results of the high religiosity test and quality of life were not compromised. The conclusion of this study is that the existence of religiosity and spirituality can provide positive coping to reduce mental disorders and improve the quality of life for students during the COVID-19 pandemic.